Edukasi kekerasan seksual dengan media video pada remaja - Astri, Hanifah; Muhani, Nova; Febriani, Christin Angelina (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Sexual violence remains a serious problem in educational settings, including secondary schools. According to data from the 2022 Symfoni PPA (PPA Children's Empowerment and Child Protection) report, there were 4,908 cases of sexual violence against children in Indonesia, with 362 cases occurring in Lampung Province. Preventing sexual violence requires effective and accessible educational efforts for adolescents. Purpose: To determine the effectiveness of sexual violence education using video media on improving students' knowledge. Method: A one-group pretest-posttest study with a randomly selected sample of 84 students. The research instrument was a knowledge questionnaire, measured before and after the intervention. Data analysis was performed using the Wilcoxon Signed Rank Test. Results: The study showed an increase in the average knowledge score from 97.26 before the intervention to 99.93 after the intervention, with a p-value of 0.001 (p<0.05), indicating a significant difference. Conclusion: Educational videos are considered effective in improving students' knowledge regarding sexual violence prevention. Routine use of video media in schools is a strategy for promoting reproductive health and preventing sexual violence against adolescents Keywords: Education; Knowledge; Sexual Violence; Video. Pendahuluan: Kekerasan seksual masih menjadi salah satu masalah serius di lingkungan pendidikan, termasuk di sekolah menengah. Berdasarkan data Simfoni PPA tahun 2022, tercatat sebanyak 4.908 kasus kekerasan seksual pada anak di Indonesia, dengan 362 kasus terjadi di Provinsi Lampung. Pencegahan kekerasan seksual memerlukan upaya edukasi yang efektif dan mudah dipahami oleh remaja. Tujuan: Untuk mengetahui efektivitas edukasi kekerasan seksual dengan media video terhadap peningkatan pengetahuan siswa. Metode: Penelitian desain one group pretest-posttest dengan sampel 84 siswa yang dipilih secara acak. Instrumen penelitian berupa kuesioner pengetahuan yang diukur sebelum dan sesudah intervensi. Analisis data dilakukan menggunakan uji Wilcoxon Signed Rank Test. Hasil: Penelitian menunjukkan adanya peningkatan rata-rata skor pengetahuan dari 97,26 sebelum intervensi menjadi 99.93 setelah intervensi, dengan p-value 0,001 (p<0,05) yang menunjukkan perbedaan signifikan. Simpulan: Video edukasi dinilai efektif dalam meningkatkan pengetahuan siswa mengenai pencegahan kekerasan seksual. Penggunaan media video dilakukan secara rutin di sekolah sebagai strategi promosi kesehatan reproduksi dan pencegahan kekerasan seksual pada remaja. Kata kunci: Edukasi; Kekerasan Seksual; Pengetahuan; Video.